Unlocking Excellence: How Teamwork and Self-Efficacy Drive Teacher Performance - Achmad Agus Priyono; Agus Widarko (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
This study aims to explore the influence of teamwork and self-efficacy on teacher performance. In the ever-evolving field of education, the role of teachers is crucial for achieving effective learning outcomes. However, many factors can affect their performance, including teamwork and self-confidence. This research employs a quantitative survey method using questionnaires distributed to several teachers in various schools. The collected data were analyzed using descriptive statistics and regression analysis techniques to evaluate the relationship between teamwork, self-efficacy, and teacher performance. The results of the analysis indicate that both independent variables, teamwork and self-efficacy, have a significant impact on teacher performance. However, partially, self-efficacy does not have a positive effect on teacher performance. These findings suggest that teachers who are confident in their abilities and can work effectively in teams tend to achieve better performance in meeting learning objectives and interacting with students. This study provides important insights into the factors influencing teacher performance and its practical implications in the educational context. The results can serve as a guide for developing strategies to enhance teamwork and self-efficacy among teachers, thereby improving the quality of education in schools.